Model Experimental Study of Damage Effects of Ship Structures under the Contact Jet Loads of Bubble in a Water Tank - Hailong Chen; Baoyu Ni; Wenjin Hu; Yanzhuo Xue (Shock and Vibration)
The damage effects of ship structures under the contact jet loads of bubble are studied by using an electric spark bubble as well as high-speed photography. A series of model experiments of ship structures under contact explosion was carried out in a water tank. On the one hand, we monitored the displacement and period of the oscillation of a hull plate of a ship model with a large bending rigidity. On the other hand, we observed the overall motion of a box-beam model with a small bending rigidity. The results show that when the distance parameter is less than 0.6, the bubble jet will impact on the surface of the structure directly, which is defined as “contact bubble jet” herein. The contact bubble jet causes significant local loads on the ship and induces the “sagging moment” effect. This mainly results from the relatively negative bending moment caused by the bubble attached to the hull. With the increase of detonation distance, this negative bending moment decreases. As a result, the oscillation amplitude of the ship structure decreases sharply and the oscillation period reduces gradually.